2010
DOI: 10.1121/1.3478784
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual sensitivity to first harmonic amplitude in the voice source

Abstract: Little is known about the perceptual importance of changes in the shape of the source spectrum, although many measures have been proposed and correlations with different vocal qualities ͑breathiness, roughness, nasality, strain…͒ have frequently been reported. This study investigated just-noticeable differences in the relative amplitudes of the first two harmonics ͑H1-H2͒ for speakers of Mandarin and English. Listeners heard pairs of vowels that differed only in the amplitude of the first harmonic and judged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
1
25
0
1
Order By: Relevance
“…This is a measure of the spectral slope of the low frequencies, and correction of the harmonic amplitudes for the effect of the first resonance of the vocal tract (F1) (Hanson, 1997) or multiple resonances (Iseli, Shue, & Alwan, 2007) has been advocated as an inverse filter to better approximate the glottal flow spectrum and compare results across vowels and speakers. H1*-H2* (the asterisk denoting corrected amplitudes) has been shown to relate to variability in the glottal pulse and spectral shapes (Kreiman, Gerratt, & Antoñanzas - Barroso, 2007), to be perceivable by listeners in the range produced by speakers (Kreiman & Gerratt, 2010), and H1-H2 can be used as a primary cue to phonemic breathiness (Esposito 2010). This measure, though, has been shown to be weak in its ability to differentiate degree of breathiness of normal and voice disordered subjects (Klatt & Klatt, 1990; Hillenbrand, Cleveland, & Erickson, 1994; Hillenbrand & Houde, 1996; Hartl et al, 2003; Holmberg et al, 2003; Shrivastav, 2003) and is influenced by nasality (Simpson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is a measure of the spectral slope of the low frequencies, and correction of the harmonic amplitudes for the effect of the first resonance of the vocal tract (F1) (Hanson, 1997) or multiple resonances (Iseli, Shue, & Alwan, 2007) has been advocated as an inverse filter to better approximate the glottal flow spectrum and compare results across vowels and speakers. H1*-H2* (the asterisk denoting corrected amplitudes) has been shown to relate to variability in the glottal pulse and spectral shapes (Kreiman, Gerratt, & Antoñanzas - Barroso, 2007), to be perceivable by listeners in the range produced by speakers (Kreiman & Gerratt, 2010), and H1-H2 can be used as a primary cue to phonemic breathiness (Esposito 2010). This measure, though, has been shown to be weak in its ability to differentiate degree of breathiness of normal and voice disordered subjects (Klatt & Klatt, 1990; Hillenbrand, Cleveland, & Erickson, 1994; Hillenbrand & Houde, 1996; Hartl et al, 2003; Holmberg et al, 2003; Shrivastav, 2003) and is influenced by nasality (Simpson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…She speculates that the linguistic status of the phonation contrast is at the heart of this difference, but her experimental design did not permit conclusions about causation. Similarly, Kreiman and Gerratt (2010) found that Mandarin listeners were significantly more sensitive to changes in H1-H2 than were English listeners (just-noticeable difference = 2.72 dB, vs. 3.61 dB). They proposed two possible explanations for this finding.…”
Section: Introductionmentioning
confidence: 79%
“…Previous work has demonstrated that listeners are sensitive to individual components of the model, particularly H1-H2 (Kreiman & Gerratt 2010) and to higher frequencies (Kreiman & Gerratt 2012). Garellek et al (2013) also found that changes to both H1-H2 and H2-H4 (but not to H4-2kHz or 2kHz-5kHz) were important for the perception of contrastive breathiness in White Hmong.…”
Section: Introductionmentioning
confidence: 85%
“…The voices were inverse-filtered and copy-synthesized to obtain a synthetic copy of the original voice that was a close perceptual match to the original. For more details of the copy-synthesis process, see Javkin et al (1987) and Kreiman et al (2010). In brief, the synthesizer's sampling rate was fixed at 10 kHz.…”
Section: Methods Voicesmentioning
confidence: 99%
See 1 more Smart Citation